An alternative osteosynthesis technique: single column anatomical plate fixation for distal humerus diaphyseal fractures - J., Benjamin Vinodh; Sathiyaseelan, Naveen; Gajendran, Vignesh; Vignesh, Arun; Rathi, Nitesh Kumar (International Journal of Research in Orthopaedics, 2023)
Background: The treatment of distal humerus diaphyseal fractures presents significant challenges for orthopedic surgeons. The goal of this study is to evaluate the effectiveness and outcomes of a single column anatomical plate as an alternative method of osteosynthesis for fixing distal humerus diaphyseal fractures. Methods: A Prospective analysis of patients who underwent surgery for distal humerus diaphyseal fractures at a tertiary care medical center was conducted. Patients who received treatment using a single column anatomical plate were included in the study. Preoperative, intraoperative, and postoperative data, including fracture type, surgical approach, complications, range of motion, and radiographic outcomes, were collected and analyzed. Results: Type B2 fractures were more common in our study i.e., 80%. The maximum incidence was between 18 to 59 years i.e., 21 cases (77%). Average radiological union was seen at 15 weeks. This study shows Excellent outcome in 67% and Good in 30% of patients. Average post-operative ROM at 1 year was mean flexion 120°(SD 7), mean extension of 6 degrees (SD 4.7), mean pronation 81.25°(SD 2.5) and mean supination 82.5°(2.8). Average MEPS score was 95.5 at 1 year. The mean metaphyseal-diaphyseal angle was 85°, the mean humeral-ulnar angle was 14°, which was within the normal limits. Conclusion: The use of a single column anatomical plate for fixing distal humerus diaphyseal fractures appears to be a promising alternative method of osteosynthesis. However, further prospective studies with larger sample sizes and longer follow-up periods are warranted to validate the efficacy and safety of this technique.